(3fXe GdOQQ hGdYbHGf aj HjGf TQa RjGf hPcQ edhcge GdCYjGf hef edc ef CSdGage ajeG eVi ef GdReGfs - (3GdJfSj , eMeO Hf YHO Gddg Hf YHO GdLdjd, CHh YHO Gddg,J (B899 (3g` s
(3ChdgG (B:s
(3Chd GdehLhO efg bhdg (B: (3hfTgO Cf dG Edg EdG Gddg hMOg dGTQjc dg hHYO MeO dGdg aEf ef CLd eG jTJZd HY NOeI ef LeY Gddg dg YR Gdedc s
(3BNQgG (B:s
(3ef bhd CHj YHO Gddg eMeO Hf XaQ ef ebWYI ChdgG (B: (3CjG efG jYhd ai GdeTcdGJ Ydi eG QCg heG OHQg ced GdbSe GdKGfi s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B238 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B222s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3GdJGQjNs